Tikanga or tokenism? : kaimahi experiences with the family group conference process : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Psychology at Massey University, New Zealand - Bradley, Jaycie (Massey University, 2023)
The Family Group Conference (FGC) emerged in response to the lack of culturally competent social work practice and institutional racism embedded within statutory policies. Ultimately, Māori were subject to statutory policies and processes that marginalised their voices and disempowered their decision-making. By introducing the FGC, tikanga (values) would be implemented into the process thus empowering whānau to take a lead role in decision-making. As a result, whānaungatanga (relationships) would be stronger as the process will be more collaborative and engaging. Inevitably, substantial change to these processes and policies have been drawn out with whānau continuing to be disadvantaged. Due to the Covid-19 pandemic, any opportunity to build or maintain whānaungatanga was severed. For whānau in the care system, this further exacerbated pre-existing challenges such as isolation from wider whānau due to the imposed social distancing requirements when whānau already suffered from disconnection. Nevertheless, an overwhelming number of tamariki and their whānau still continue to enter the care system. For many this has become an intergenerational “normality” of experiencing the same trauma. Expectedly, whānau have grown distrustful of the system and the professionals, often revoking engagement. In order to understand what barriers there are in the current FGC process, a comprehensive insight into the realities of those on the frontline is necessary. The present research addresses this knowledge gap through amplifying the voices of the community kaimahi (workers) who operate the space between statutory and community. Often overlooked by other agencies and labelled as “non-qualified,” kaimahi harbour an incredibly valuable and rich array of knowledge due to their constant engagement with the whānau they support. Adopting a Kaupapa Māori research, ethnographic approach whilst drawing from elements of autoethnography, the experiences of three kaimahi were explored. Insights into how they perceive the FGC and locate themselves within a network of relationships and narrative were gained through go-along interviews and a reflective research journal. Drawing from two forms of Māori narrative analysis: Pūrakau and Kaupapa Kōrero, this permitted a vast range of considerations. Affirming whānau as decision-makers during this process and promoting a Te ao Māori process encompassing a range of traditional practices is pivotal to enhancing the mana of whānau and pathways out of the care system. Future research derived from Kaupapa Māori principles is necessary to invoke meaningful change.
Keywords: Māori Masters Thesis; 451015 Te hauora me te oranga tūmatanui o te Māori (Māori public health and wellbeing)